IgAN its clinical presentatio - Yaqub, Sonia (Pakistan Journal of Kidney Diseases, 2022)
Background: Clinical presentation, kidney biopsy findings and clinical outcomes of IgA nephropathy (IgAN) are highly variable. The objective of this study is to study the clinical presentation, histologic patterns and outcomes of IgAN in Pakistani population, as no significant data is available in international literature from this part of the world. Material and Methods: A retrospective chart review was conducted of all patients with biopsy proven IgAN between January 2007 and December 2017.